1997
DOI: 10.1038/bjc.1997.359
|View full text |Cite
|
Sign up to set email alerts
|

Fas receptor is expressed in human lung squamous cell carcinomas, whereas bcl-2 and apoptosis are not pronounced: a preliminary report

Abstract: Summary We report a pilot study on the Fas receptor (APO-1, CD95) in vivo in 15 human squamous cell (non-small) carcinomas and ten normal bronchial specimens. The principal aim was to investigate whether the so-called death receptor, Fas, is present in these tumours. Ligation of Fas promptly induces apoptosis, particularly in T Jurkat cells in vitro, and expression of Fas on human cancer would thus theoretically be of great interest. The immunoreactivity for the anti-apoptotic protein Bcl-2 was also investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
2

Year Published

1998
1998
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 28 publications
0
12
0
2
Order By: Relevance
“…Human Fas antigen consists of 325 amino acids and transduces death signal conferred by anti-Fas antibody or Fas L. Fas expression was reported in various kinds of human malignancies, including ovarian serous cystadenocarcinoma (OwenSchaub et al, 1994;Hellquist et al, 1997;Wakahara et al, 1997). In our study, 74% of patients with ovarian neoplasms showed Fas expression without significant difference in the frequency of Fas expression between histologic types.…”
Section: Discussionmentioning
confidence: 56%
“…Human Fas antigen consists of 325 amino acids and transduces death signal conferred by anti-Fas antibody or Fas L. Fas expression was reported in various kinds of human malignancies, including ovarian serous cystadenocarcinoma (OwenSchaub et al, 1994;Hellquist et al, 1997;Wakahara et al, 1997). In our study, 74% of patients with ovarian neoplasms showed Fas expression without significant difference in the frequency of Fas expression between histologic types.…”
Section: Discussionmentioning
confidence: 56%
“…Hellquist et al 32) reported Fas expression in all of eight lung squamous cell carcinomas using immunohistochemistry. Nambu et al 33) also reported the expression of Fas protein in 20 of 42 lung adenocarcinoma tissues (47.6%), and sFas mRNA in four of seven tumor samples.…”
Section: Discussionmentioning
confidence: 99%
“…20 Previously, it has been shown that squamous cell carcinomas of the tongue and oral cavity, lung, and squamous cell carcinoma cell lines express Fas. [21][22][23][24] In a recent study, however, Fas expression in ESCCA was found to be heterogeneous and essentially absent in the majority of cases, although it was expressed in the Immunoperoxidase staining was done with hematoxylin counterstaining (original magnification ϫ100).…”
Section: Discussionmentioning
confidence: 99%